ANALISIS ATURAN PEMERlNTAH MENGENAI MEREK DALAM MEMBERlKAN PERLlNDUNGAN HUKUM TERHADAP UMKM - Putri, Monica Permata; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
MSMEs play a vital role in Indonesia's economic=growth. Like large industries, MSMEs must also pay attention to Intellectual Property Rights, especially trademarks. Trademark registration is important to avoid plagiarism and obtain legal protection from the government. However, many MSMEs have not registered their trademarks due to limited capital and lack of understanding of the benefits of trademarks. Therefore, regulations are needed to protect MSME brands. This research aims to evaluate government policy in providing legal protection for MSMEs using normative juridical methods. The research results show that government policies include various conveniences for brand registration at lower costs for MSMEs, collaboration with the Director General of IP at the Ministry of Cooperatives and MSMEs, providing incentives for MSME brand registration fees, as well as collective brand registration for the MSME industry.Keywords : Kekayaan Intelektual, Pemerintah, Pendaftaran Merek, UMKM.